The theory in practice of teaching languages to foreigners. (Eurasian Journal of Philology Science and Education, 2015)
The article describes the activities of scientific and methodological schools of mastering a foreign language, based at the Department of foreign language training of the Al-Farabi Kazakh National University 30 years ago.Scientific works of the team, published articles and monographs utilised in textbooks is a symbiosis of science and practice, constituting a main scientific platform of the language learning theory KazAF and RAF in Kazakhstan. The article notes that the main purpose of mastering a foreign/second language today are not only linguistic competence associated with the mastery of all kinds of speech activity, but also the ability of the inophones to communicate interactively, learning the practical application of acquired language skills, familiarity with cross-cultural and cultural realities. The article analyzes the collective technologies of the department staff to ensure effective conditions for the formation of both communicative and intercultural competence of inophones.
Keywords: theory of language learning; language and intercultural competence of inophones